Rebuilding the Hungarian-Romanian Border Zone as a Learning Region (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2017)
Although there is no straightforward definition for the concept of learning regions, it is still subject of a worldwide intensive research. As a general approach, we could affirm that it embodies the territorial application of the knowledge economy in its evolution. One also have to notice that the study of these entities constitutes a very dynamic subfield of regional studies. In this sense, our paper applies some of the results obtained in this field of research to the Hungarian-Romanian border zone. This region, although divided since almost a century by a state frontier, still inherits several features from the pre-WWI period. On the other hand, after the fall of communism, old ties were rebound, especially in the form of trans-frontier co-operation. Both halves of the area do benefit from a quite well developed infrastructure, industrial and tertiary facilities, as well as important educational and cultural institutions. There exists a quite solid network of big and small towns, each of them with its own agglomeration area, trying to rebind the old lines of influence. In our study, we also examine the possibilities of using these advantages combined with the post-1989 experience in transforming this area into a learning region.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.